Evaluate adherence to quality indicators in managing acute pancreatitis at a tertiary care hospital - Quddusi, Maida Binte Khalid; Sohail, Zahabia; Shaikh, Hafsa; Jawed Qureshi, Neelam; Parkash, Om (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the quality of acute pancreatitis management by evaluating adherence to the quality indicators of a standardised international clinical guideline. Method: The retrospective observational study was conducted from September 1, 2022, to March 31, 2023, at the Aga Khan University Hospital, Karachi, and comprised data of adult inpatients diagnosed with acute pancreatitis from January 2018 to December 2022. Data was collected from the departments of Gastroenterology, Surgery and Emergency Medicine. A quality checklist with 10 indicators and 5 measures following clinical guidelines from the Acute Pancreatitis Task Force on Quality to make comparative assessments. Data was analysed using SPSS 24. Results: Of the 150 patients with a mean age 50.47+/-18.25 years, 82(54.7%) were females. Diagnosis was based on clinical symptoms 124(82.7%) and enzyme levels 26(17.3%). Aetiology remained unknown in 65(43.3%), and 30(46.1%) underwent further imaging. Fluid resuscitation 149(99.3%) and timely endoscopic retrograde cholangiopancreatography for cholangitis 22(78.6%) were common. Biliary pancreatitis 69(46%) was also common. Nutrition 141(85.3%) and pain management 147(98%) adhered to the guidelines. Complications led to more imaging 25(71.4%), and necrotising pancreatitis was treated with minimally invasive interventions. Overall adherence to guidelines ranged from 95 to 150 (63.7-100%). Conclusion: There was a considerable level of adherence to guidelines in several acute pancreatitis management aspects. However, areas for improvement existed, notably in aetiology determination and imaging utilisation. Keywords: Acute pancreatitis, Quality indicators, Treatment outcome, Endoscopic retrograde cholangiopancreatography.